Supporting Personalized Learning through Individualized Learning Plans. Issue 1 (4th March 2019) - Hackmann, Donald G.; Malin, Joel R.; Fuller Hamilton, Asia N.; O'Donnell, Laura
Abstract: Individualized Learning Plans (ILPs), an effective strategy to promote students' college and career readiness, are increasingly used in US school systems as a mechanism to encourage students' career exploration and identification of career goals. After describing features of ILPs, we provide an example of the ILP process developed and implemented in the junior high schools in McLean County (Illinois) Unit District No. 5. Based upon this experience, we share important factors for school leaders that can affect successful implementation in their schools.